2020
DOI: 10.1088/1742-6596/1485/1/012006
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Amylase-Producing Amylolytic Bacteria from Rice Soil Samples

Abstract: Amylase is an enzyme that plays a role in hydrolyzing starch to simple sugars. This protein is very important for various industrial processes. Microorganisms are considered as the best source of amylase production. This study was aimed at isolating and dentifying amylolytic bacteria from rice soil samples that have the potential to produce amylase enzymes. Rice soil samples were collected from two locations, namely the Percut Sei Tuan area and Labu Beach. Samples was isolated, then macroscopically identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 5 publications
0
7
0
1
Order By: Relevance
“…When examined under a microscope, the results of endospore staining in both B. subtilis (UPMB10) and the mixed strains of bacteria reveal a dark green colour, indicating the presence of endospores. An endospore is a structure that can withstand harsh environmental conditions such as dryness, heat, and acidity (Rattray et al, 2021;Silaban et al, 2020). Endospores are extremely thick and refractile due to their low water content (Tehri et al, 2018).…”
Section: Bacillus Subtilis Endospores Detection After 12 Months Of Sh...mentioning
confidence: 99%
“…When examined under a microscope, the results of endospore staining in both B. subtilis (UPMB10) and the mixed strains of bacteria reveal a dark green colour, indicating the presence of endospores. An endospore is a structure that can withstand harsh environmental conditions such as dryness, heat, and acidity (Rattray et al, 2021;Silaban et al, 2020). Endospores are extremely thick and refractile due to their low water content (Tehri et al, 2018).…”
Section: Bacillus Subtilis Endospores Detection After 12 Months Of Sh...mentioning
confidence: 99%
“…This remains a substantial difference in the kinds of indigenous microorganisms extracted from distinct different host plants. Bacterial isolates are distinguished by their colors and colony shape [42,43]. A previous study was revealed the identification of BE from tomato [44],…”
Section: Diversity Of Bacteria From Citrusmentioning
confidence: 99%
“…Amylases are a group of hydrolytic enzymes which hydrolyze the glycosidic linkages of starch and related polysaccharide molecules to produce simpler sugar molecules, such as glucose, maltose, and dextrin (My et al 2022;Silaban et al 2020). They are classified into three types comprising -amylase (1,4-α-D-glucan glucanohydrolase or glycogenase), -amylase (1,4-α-D-glucan maltohydrolase, glycogenase, or saccharogen amylase), and -amylase (glucan 1,4-α-glucosidase, amyloglucosidase, exo-1,4-α-glucosidase, glucoamylase, lysosomal αglucosidase, or 1,4-α-D-glucan glucohydrolase) based on the different mechanisms of the glycosidic linkage hydrolysis (Benjamin et al 2013;Joshi et al 2021).…”
Section: Introductionmentioning
confidence: 99%